Interfacial dynamics and thermal behaviour of a 5%v/v butanol/water droplet impacting a hot surface - Arif Widyatama; Tito Shantika; Indarto; Deendarlianto (University of Muhammadiyah Malang, 2025)
Efficient cooling at high surface temperatures remains challenging because droplet surface interactions and the associated heat transfer mechanisms are not yet fully understood. The present experimental study aims to investigate the impact dynamics and transient heat transfer characteristics of a single binary droplet impinging on a heated surface under different wall temperature conditions. A butanol/water droplet was deposited onto an Inconel 718 under a horizontal configuration. High-speed visualisation was used to capture droplet behaviour, while the wall temperature was measured at the centre of the specimen to evaluate the cooling performance. Experiments were conducted for initial wall temperatures ranging from 85 °C to 195 °C. The results show that droplet spreading and recoiling dominate the cooling process at low wall temperatures, leading to limited heat transfer enhancement. At higher wall temperatures, pronounced interfacial disturbances and internal droplet motion occur, resulting in a marked increase in heat transfer. Despite the intensified vapour activity, the droplet maintains surface wetting, allowing sustained heat transfer without dry-out. The findings demonstrate the importance of interfacial dynamics in droplet-based cooling at high wall temperatures.